Local Self-Governance in Antiquity and in the Global South - Krüger, Dominique; Mohamad-Klotzbach, Christoph; Pfeilschifter, Rene (2022)
Society begins at the local level. This interdisciplinary volume analyzes different kinds of local self-organization against the backdrop of the rather limited states of Antiquity and the Global South of the present. By collaborating across different periods of time the contributors get a better grasp of the mechanisms by which local governance succeeds, and advance the theoretical debate on state and society.